Front-line imatinib treatment in children and adolescents with chronic myeloid leukemia: results from a phase III trial - Suttorp, Meinolf; Schulze, Philipp; Glauche, Ingmar; Göhring, Gudrun; von Neuhoff, Nils; Metzler, Markus; Sedlacek, Petr; de Bont, Eveline S J M; Balduzzi, Adriana; Lausen, Birgitte; Aleinikova, Olga; Sufliarska, Sabina; et al. (Leukemia, 2018)
A total of 156 patients (age range 1.3-18.0 years, median 13.2 years; 91 (58.3%) male) with newly diagnosed CML (N = 146 chronic phase (CML-CP), N = 3 accelerated phase (CML-AP), N = 7 blastic phase (CML-BP)) received imatinib up-front (300, 400, 500 mg/m2, respectively) within a prospective phase III trial. Therapy response, progression-free survival, causes of treatment failure, and side effects were analyzed in 148 children and adolescents with complete data. Event-free survival rate by 18 months for patients in CML-CP (median follow-up time 25 months, range: 1-120) was 97% (95% CI, 94.2-99.9%). According to the 2006 ELN-criteria complete hematologic response by month 3, complete cytogenetic response (CCyR) by month 12, and major molecular response (MMR) by month 18 were achieved in 98, 63, and 59% of the patients, respectively. By month 36, 86% of the patients achieved CCyR and 74% achieved MMR. Thirty-eight patients (27%) experienced imatinib failure because of unsatisfactory response or intolerance (N = 9). In all, 28/148 patients (19%) underwent stem cell transplantation (SCT). In the SCT sub-cohort 2/23 patients diagnosed in CML-CP, 0/1 in CML-AP, and 2/4 in CML-BP, respectively, died of relapse (N = 3) or SCT-related complications (N = 2). This large pediatric trial extends and confirms data from smaller series that first-line imatinib in children is highly effective.
Keywords: kombinovaná terapie; Bone Marrow; Humans; Infant; inhibitory proteinkinas; kojenec; imatinib mesylát; dítě; Disease Progression; Child; Imatinib Mesylate; Female; Antineoplastic Agents; výsledek terapie; lidé; Biomarkers; mladiství; předškolní dítě; Protein Kinase Inhibitors; Neoplasm Grading; staging nádorů; biologické markery; ženské pohlaví; Male; chronická myeloidní leukemie; Adolescent; prognóza; Treatment Outcome; stupeň nádoru; kostní dřeň; protinádorové látky; progrese nemoci; Neoplasm Staging; Combined Modality Therapy; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; mužské pohlaví; Treatment Failure; Child, Preschool; Prognosis; neúspěšná terapie